Pengaruh Pandangan ABH (Anak yang Berhadapan dengan Hukum) mengenai Pemenjaraan terhadap Konsep Diri, Pengungkapan Diri, dan Motivasi Belajar ABH - Khatarina Ika Pramelianti; S. Rouli Manalu (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
ABH is serving a sentence by being placed in LPKA to be given training so that their psychological conditions including self-concept, self-disclosure, and learning motivation remain good. Meanwhile individuals who are convicted or sent to prison tend to have poor psychological conditions. The research aims to determine whether there is an influence between the views regarding imprisonment on ABH’s self-concept, self-disclosure, and learning motivation. The research uses the Total Institution Concept which explains the experience of individuals in the total institution influencing the self-concept, self-disclosure, and prisoners' motivation to be productive. Simple linear regression statistical test is used to determine the effect of 1 independent variable on 1 dependent variable. The study was conducted in LPKA Kutoarjo by using a total sampling of 51 respondents. The results showed that there was a positive influence between ABH's views of imprisonment on self-concept by 9% with a significance value (0.0340,05) and learning motivation with a significance value of (0.256>0.05). It can be concluded that the hypothesis stating there is an influence between ABH's views regarding imprisonment on ABH's self-concept was accepted. While the hypothesis which states there is an influence between ABH's views regarding imprisonment on self-disclosure and ABH's learning motivation is rejected. The findings show ABH have a good self-concept, they often do self-disclosure and have high motivation to learn.